Repurchase Intention of Halal Culinary Mie Gacoan: Experience Satisfaction with Site Image and Content Moderation - Nur 'Aeni; Surya Bintarti; Salina; Dede Nur Iskandar; Suhrowardi (JPIES: Jurnal Pelita Ilmu Ekonomi Syariah, 2025)
This study aims to analyze how Experience Satisfaction influences Revisit Intention, moderated by Site Image & Content among Generation Z consumers of Mie Gacoan. This study uses a quantitative approach with primary data sources. A total of 250 participants were selected as the sample using Purposive Sampling based on the Non-Probability Sampling method. The collected data were analyzed using the Partial Least Square - Structural Equation Modeling (PLS-SEM) statistical tool. The results of the study indicate that: 1) Experience Satisfaction has a positive and significant effect on Revisit Intention among Generation Z consumers of Mie Gacoan; 2) Site Image does not moderate the relationship between Experience Satisfaction and Revisit Intention among Generation Z consumers of Mie Gacoan; 3) Content also does not moderate the relationship between Site Image and Revisit Intention among Generation Z consumers of Mie Gacoan.